Pengaruh Proses Austempering Terhadap Sifat Mekanik Dan Struktur Mikro Baja AISI 4140 - Purnomo, Purnomo; Muhammad, Badarruddin; Sugiyanto, Sugiyanto; Zulhanif, Zulhanif; Nafrizal, Nafrizal (TURBO [Tulisan Riset Berbasis Online], 2023)
Tensile, impact, and hardness specimens were prepared from the round bar AISI 4140 steel with a diameter of 16 mm. All specimens were subjected to annealing heat treatment by heating in the electrical furnace at 800C for 2 hour and later cooled in the furnace until the specimens temperature reached room temperature. After annealing treatment, all specimens were ultrasonically washed using acetone. Furthermore, each specimen was given the austempering treatment by firstly heating at 800C in an induction coil heater for 10 minutes, then quickly immersed into a salt bath at 312C for 1 hour, and later cooled at room temperature. The hardness of the steel in annealing condition is about 24.33 HRC. The hardness of the steel in austempering increases significantly by about 72.63%. The impact energy of the annealed and austempered steels is about 17.33 joules and 37.67 joules, respectively. A similar increase in yield strength of the AISI 4140 steel from 316.6522 MPa (annealing condition) to 533.7562 MPa (austempering condition). The microstructures of the annealed steel are dominant pearlite and ferrite, then after austempering treatment, the bainite, martensite, and residual austenite phase are formed in the microstructure of the steel. The fractural surface of annealed steel is dominated by brittle and ductile fractures with relatively large grain sizes. On the other hand, by austempering treatment, the fractural surface morphologies of steel exhibit the tendentious-ductile type accompanied by an small amount of brittle fracture in fine grain size area.